Analisis Dampak dari Pembangunan Green Building : Studi Literatur - Nike Meydita Nuur Hidayah; Catlya Noer Aime Salwanaina; Muhammad Hamzah Fansuri (Arsir: Jurnal Arsitektur, 2026)
The application of the green building concept is a sustainable solution to reduce negative impacts on the environment while optimizing the efficiency of resource use.. This study analyzes the impact of implementing the concept in four main aspects, namely environment, economy, health and safety, and energy efficiency. By utilizing energy-saving technology, environmentally friendly materials, and renewable energy, sustainable buildings can reduce dependence on non-renewable resources. The results of the study show that the adoption of sustainable buildings contributes significantly to overcoming climate change and creating a healthier and more sustainable environment. In addition, this study also explores the role of digital libraries in supporting learning and providing reliable information. The analysis was conducted based on energy efficiency, environmental impact, economic impact, and health and safety that occurred in the construction of green buildings. This study uses a systematic literature review approach, with sources from journals and articles indexed by Scopus and Google Scholar in the last twenty year. The results of the study show that digital libraries help maintain the validity of information and facilitate access to knowledge. This facility simplifies the process of learning, research, and developing science more optimally.